PEMBENTUKAN KARAKTER ISLAMI MELALUI PEMBIASAAN JUMAT TAKWA SISWA DI SDN 5 KOMET BANJARBARU - Nurhidayani Yeni; ulfah, Aunia Ulfah; Yonisa, Tri Yonisa; Fitriani Aspahani (Almarhalah: Jurnal Pendidikan Islam, 2025)
This study explores the role of religious upbringing in shaping Islamic character  among students in schools.By examining the integration of religious practices into daily routines , the study aims to understand how consistent  exposure to religious teachings influences the development of Islamic values and behaviour . Through a comparative  analysis of educational approaches in Indonesia, this  research investigates the methods employed to instill religious values within the school environment. Findings suggest that a combination of curriculum content,extracurricular activities, and teacher-student  interactions significantly contribute to the cultivation of Islamic character. The study underscores the importance of incorporating religious teachings into educational frameworks to foster  a strong foundation of Islamic ethics and morality among students.